2018
DOI: 10.3390/catal8110536
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Catalytic Combustion of Methane in a Microcombustor with Metal Foam Monolithic Catalyst

Abstract: Utilizing catalysts in microcombustors is probably an excellent practical solution to stabilize fuel combustion because of the relatively fast reaction speed. In the present work, the monolithic catalyst Pd/A2O3/Fe-Ni with metal foam as matrix was used inside a 5 mm in diameter microcombustor. Then the effects of inlet velocity and equivalent ratio on catalytic combustion characteristics of methane were studied experimentally. The results showed that the methane and air mixture with the stoichiometric ratio Φ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…13 Catalysts with higher surface-to-volume ratio promote more sites for the adsorption of fuel and oxidizer. 14 Hence, catalytic combustion can improve flame stability and conversion efficiency in microcombustors. Li et al conducted a numerical analysis to study the geometry and flame temperature on a methane air-premixed microcombustion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Catalysts with higher surface-to-volume ratio promote more sites for the adsorption of fuel and oxidizer. 14 Hence, catalytic combustion can improve flame stability and conversion efficiency in microcombustors. Li et al conducted a numerical analysis to study the geometry and flame temperature on a methane air-premixed microcombustion.…”
Section: Introductionmentioning
confidence: 99%
“…Slotted or controllable slotted bluff body catalytic microcombustors have been shown to exhibit better combustion performance with stable flame when the gap width is maintained at 0.6 mm 13 . Catalysts with higher surface‐to‐volume ratio promote more sites for the adsorption of fuel and oxidizer 14 . Hence, catalytic combustion can improve flame stability and conversion efficiency in microcombustors.…”
Section: Introductionmentioning
confidence: 99%
“…Qu and Feng ( 2015 ), Feng and Qu ( 2016 ) studied the catalytic combustion of premixed methane/air in a two-zone perovskite-based alumina (Al 2 O 3 ) pileup-pellets burner, and indicated that the flame stability limits increased with the increase of equivalence ratio or pellet diameter. Li et al ( 2018 ) used a metal foam catalyst to catalyze methane (CH 4 ) combustion in a micro-combustion chamber and investigated the effects of inlet velocity and equivalence ratio on catalytic combustion characteristics of methane. These results show that a mixture of methane/air has an equivalent ratio of 1.0 and that a mixed fuel with an inlet velocity of 0.2–0.6 m/s can achieve combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Several Pd catalysts have also been developed using other supports. Liu et al [10] developed a rice husk derived porous silica support for a Pd-CeO 2 catalyst for low temperature combustion of methane with 90% conversion at 325 • C. A monolithic Pd/Al 2 O 3 /Fe-Ni catalyst with metal foam as matrix in a microcombustor improved methane conversion to more than 99% [11]. Cargnello et al [12] developed a novel Pd@CeO 2 /hydrophobic-Al 2 O 3 core-shell catalyst that had methane conversions of 50% and 100% at 325 • C and 400 • C respectively.…”
Section: Introductionmentioning
confidence: 99%